Translanguaging in the Communicative Practice of Buyers and Sellers in Traditional Market - Munirah, Munirah; Thaba, Aziz; Yusuf, Akram Budiman (Indonesian Journal of Applied Linguistics, 2021)
The purpose of this study is to examine the translanguaging practice of buyers and sellers in a traditional market in Palopo, South Sulawesi, Indonesia. Translanguaging is a relatively new term in contemporary linguistics. By using the qualitative method, this current study presents an alternative perspective to describe the existence of discrete languages and multilingualism by combining different language features and offers a critical assessment of the theory of bilingualism proposed by Waring (2013) and Garcia and Otheguy (2014) by drawing upon empirical data at our disposal. This study indicates some insightful characteristics of translanguaging practice performed by buyers and sellers. It consists of types, forms, functions, and factors. Firstly, the types of translanguage practices are internal, foreign words, and hybrid aspects. Secondly, this study managed to categorize the practice of translanguage in buyers’ and sellers’ interactions in three features, namely basic word insertions, invented word insertions, loan word insertions, phrase insertions, reduplications, and regional language particle insertions. This study is not intended to challenge or reject code-switching analyses previously reported by other scholars. However, it challenges the way those scholars’ view this real sociolingustic language phenomenon through the theory of translanguaging. In summary, a multilingual community such as a traditional market in Palopo, South Sulawesi, represents the emergence of an awareness of language users to entertain social, cultural, and political entities in the practice of communication. Such awareness is reflected in people’s translanguaging structural utterances in their exchanges.